1993
DOI: 10.1021/ja00058a014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin monolayer lipid membranes from a new family of crown ether-based bola-amphiphiles

Abstract: 1705 timum values of the parameters of this equation to fit the conductance kinetic data, Le., the values of [HX],. and ti. Because of interdependencies, all five parameters k , , k2, k3, to, and [HX], could not be accurately determined simultaneously; therefore, calculations were done with fixed values assigned for either one or both of k2 and k3. The program can also be used to calculate first-order rate coefficients where the parameters are k3, to, and [HX], with k , and k2 set to 0.It was determined from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…Azacrown-based lariat ethers [49,19] proved versatile and flexible. In separate studies, it was found that crown ethers function well as amphiphilic headgroups [50,51]. Crown ethers are, of course, cation selective and it was thought that some selectivity would be imposed on the system if cations used the crown as an entry portal.…”
Section: Design Criteria For Hydraphilesmentioning
confidence: 99%
“…Azacrown-based lariat ethers [49,19] proved versatile and flexible. In separate studies, it was found that crown ethers function well as amphiphilic headgroups [50,51]. Crown ethers are, of course, cation selective and it was thought that some selectivity would be imposed on the system if cations used the crown as an entry portal.…”
Section: Design Criteria For Hydraphilesmentioning
confidence: 99%
“…Munoz et al 14 and Brisset et al 15 reported a significant impact of the length of the hydrophobic linkage on the aggregation properties of bolaamphiphiles with crown ether or sugar heads. These authors suggested a bending of chains consisting of 12 methylene groups or more.…”
Section: Figure 1 Structures Of Micelles and Vesicles Formed By Bolamentioning
confidence: 99%
“…21 Such results are in very good agreement with the hypothesis that the hydrophobic segment folds up when bolaform surfactants bear a long hydrocarbon spacer arm. 14,15 However, it is noteworthy that the rigidity of the linker in compounds B2 and B4, afforded by a biphenyl or fluorocarbon chain, did not prevent micelle formation and thus, probably, the folding up of the spacer group.…”
Section: Issn 1424-6376mentioning
confidence: 99%
“…Examples of these include liposomes [1], polymersomes [2,3] and niosomes [4,5]. Other vesicle-like structures include colloidosomes, whose membranes are not necessarily made up of bilayers of amphiphiles [6,7].…”
Section: What Are Vesicles?mentioning
confidence: 99%